Shaykh Al-Zamakhshary's Interpretation of Ru'yatullah (Study of Interpretation of Al-Qur'an Surah Al-Qiyamah Verses 22-23 in Kitab Al-Kasysyaf) - Shb, Khoirul Fadly; Nasution, Muhammad Roihan; Simamora, Nuraisah; Sitanggang, Cokro Malik (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to discuss how the interpretation of Al-Zamakhshary, a great scholar of the Mu'tazilah school, on how to see Allah contained in Qs. al-Qiyamah/75: 22-23 with reference to his tafsir Al-Kasysyaf. Seeing is called by the term Ru'yatullah. Ru'yah comes from the word رأ ى – يرى – رأ ي – رأية which means to see, to be sure, to suppose, and to think. What is meant by seeing here is seeing Him in the afterlife. The author uses qualitative research methods in this study, using the type of library reasearch with a descriptive approach. Therefore, the author examines the meaning and interpretation of the verses of ru'yatullah. This is done through the tahlili method, which is used to analyze data related to al-Zamakhshary's interpretation of ru'yatullah in surah al-Qiyamah verses 21-22. In this study the author found that al-Zamakhshary negates Ru'yatullah (seeing Allah) in the afterlife. Al-Zamakhshary ta'wil-kan the word ناظر ة in surah al-Qiyamah verse 23, with the meaning of "al-intizar", so the meaning of the verse above is waiting for rewards and enjoyment from Allah, not seeing Allah in the hereafter.